Electricity markets in transition: A multi-decade micro-model of entry and exit in advanced wholesale markets - Peter C. Cramton; Emmanuele Bobbio; David Malec; Pacharasut Sujarittanonta (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Electricity markets worldwide are undergoing a many-decade transition in the way electricity is generated and consumed. The success of this transition depends critically on climate policy and market design. We model the most advanced electricity markets in the world to evaluate the impact of alternative policies on electricity market outcomes over the next 40 years, including costs, profits, social welfare, risks, and reliability. Each year, investors decide which resources enter and exit given forward-looking consistent expectations about energy profits, prices, and costs. The model is unique in modeling investment decisions at the individual unit level based on precisely calculated profits from energy, reserves, and capacity markets. These profits depend critically on the resource structure, which changes each year with investor decisions. New and essential elements of electricity markets, such as battery storage and price responsive demand are fully integrated. The model provides detailed insights into how policies such as carbon pricing impact the transition to renewable energy.
Keywords: 330